h.hofstede (h.hofstede@hogeland.nl)

       
1. a. u = (x + 1)1/3
(x + 1) = u3
x = u3 - 1
x' = 3u2
   
    Dat is dan  0,6(x + 1)5/3 + 4,5(x + 1)2/3 + c
       
  b. u = (x - 2)1/2
x - 2 = u2
x = 2 + u2
x ' = 2u
   

    Dat is dan  6(x - 2)0,5 - 8/3(x - 2)1,5 + 2/5(x - 2)2,5 + c
       
  c. u = lnx
x
= eu
x
' = eu
   
    Dat is dan  2√(lnx) + c
       
2. a. u = x1/3
x = u3
x' =3u2
 
       
   
       
  b. u = (1 + x)0,5
u2 = 1 + x
x = u2 - 1
x ' = 2u
 
       
   
       
  c. x0,5 = u
x
= u2
x' = 2u
 
       
   
   

h.hofstede (h.hofstede@hogeland.nl)